Roads and Rural Development in Sub-Saharan Africa - Berg, Claudia N.; Blankespoor, Brian; Selod, Harris (World Bank, Washington, DC, 2016)
This paper assesses the relation between access to markets and cultivated land in Sub-Saharan Africa. Making use of a geo-referenced panel over three decades (1970-2005) during which the road network was significantly improved, the analysis finds a modest but significant positive association between increased market accessibility and local cropland expansion. It also finds that cropland expansion, in turn, is associated with a small but significant increase in local gross domestic product. These results are suggestive of agricultural activities that develop at the extensive margin, which are mostly to serve local demand, but are not indicative of commercial agriculture that serves external markets.